Factors for the success of public policy implementation of the integrated economic and social upgrade project per sub-district 1 sub-district 1 university (university to sub-district) building a glass root for the country) in the area of Khok Klang Subdis - Promkaew, Wichian; Permpoon, Athimat (Journal for Developing the Social and Community, 2023)
This research article aims to study the management and success factors of public policy implementation of the project to enhance the economic and social integration of each sub-district, 1 sub-district, 1 university (university to sub-district). building a glass root for the country) in the area of ​​Khok Klang Subdistrict Phanom Dong Rak District Surin The researcher has designed and developed the research process. starting from the study of the theoretical framework with document research by reviewing the literature and related research to synthesize the content of the content. and to examine the study of ideas for credibility and weight to lead to analysis. After that, an exploratory conceptual framework was studied with a pilot study. The researcher has selected the target group. Obtained by selective selection 34 people. It is an informal in-depth interview with people who have direct experience. and those involved in the management and success factors of the project (Kenaphoom, Sanya, 2014C, p. 13-32) To extract lessons or take off experiences in management and the success factors of the project which is the study of concepts from the fundamental theory Then make a theoretical conclusion. with rational thinking techniques by means of integrating a variety of methods From the research results, it was found that 1) Project management By appointing an operational committee, planning work, assigning work, coordinating operations in the area with other departments, supervising, monitoring work by field visits and reporting results. and 2) the success factor of public policy implementation, the project to enhance the economy and society by integrated sub-district, 1 sub-district, 1 university (university to sub-district) building root for the country) consisting of 6 factors as follows: 1) target factor for solving the poverty problem of the community 2) factor for the target population and coverage 3) factor for work and activities in the community Problem solving 4) Technology factors used 5) Factors involved in the agency 6) Factors about roles and duties of the organization or group of organizations that are responsible for the main and and 7) operational factors and changes occurring. This is a factor that affects the success of driving the policy into action. Keywords : Success Factor, Public Policy, Integrated Subdistrict Economic and Social Upgrading Project, 1 Subdistrict 1 University, Khok Klang Subdistrict.